2022
DOI: 10.1002/cre2.635
|View full text |Cite
|
Sign up to set email alerts
|

Candida species detection in patients with chronic periodontitis: A systematic review and meta‐analysis

Abstract: Objectives: To assess the Candida species occurrence rate and concentration in periodontal pockets in chronic periodontitis (CP) by meta-analysis. Materials and Methods:A search was performed of articles published between January 1, 2010, and October 1, 2020, in English and in Russian, in the electronic databases MEDLINE-PubMed, Google Scholar, The Cochrane Library, ClinicalTrials.gov, Research Gate, eLIBRARY, and Cyberleninka (PROSPEROCRD42021234831). The odds ratio (OR), standardized mean difference (SMD), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…This finding is consistent with a systematic review, which showed that Candida spp. may increase the risk of periodontal disease development by 1.76 times [ 47 ]. Candida albicans can interact with periodontopathic pathogens to develop mixed biofilms, suggesting that fungi may play an active role in the inflammatory destructive process during the onset and progression of periodontal diseases [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a systematic review, which showed that Candida spp. may increase the risk of periodontal disease development by 1.76 times [ 47 ]. Candida albicans can interact with periodontopathic pathogens to develop mixed biofilms, suggesting that fungi may play an active role in the inflammatory destructive process during the onset and progression of periodontal diseases [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…One aspect we should acknowledge also as a limitation is the lack of information regarding the periodontal health of the patients, which might have had an impact on the colonization of Candida sp. When the close association between C. albicans and chronic periodontitis is taken into consideration [72,73], the presence of periodontitis and poor oral health might alter the abundance of C. albicans and, due to morphogenetic similarity, of C. tropicalis in mild/moderate dysplasia, carcinoma in situ, and OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Во всех образцах преобладали представили таксономической группы Streptococcus. У обеих групп распространенность таксономической группы Streptococcus составила 23,86% (I группа) и 22,91% (II группа), что в среднем ниже нормального уровня Streptococcus и может косвенно свидетельствовать о снижении иммунного статуса [ 1 ] .…”
Section: терапияunclassified
“…Помимо пародонтальных патогенов, зубной налет содержит другие бактерии, а также грибы, роль которых активно изучается. Многие исследователи считают, что дрожжеподобные грибы, в частности Candida spp., являются одной из важных причин развития, прогрессирования и осложненного течения ХГП [ 1 ] -они условно-патогенны, колонизируют слизистую оболочку рта и кожу здоровых людей, а также считаются предупредительным признаком иммунного расстройства. Этот условно-патогенный микроорганизм длительное время может персистировать в разных нишах рта без клинических проявлений, однако при снижении иммунного статуса (например, у пациентов с сахарным диабетом или иммунодефицитом, у детей раннего возраста или у пожилых людей) или при изменении окружающей среды его факторы вирулентности могут вызывать заболевание.…”
Section: Introductionunclassified